Exploring the Impact of Music Tempo on Preschool Children's Artistic Expression: A Multisensory Perspective - Önder Yağmur; Caner Şengünalp; Nurşen Osmanoğlu; Mehmet Arif Karamanoğullari; Mehmet Burhan Çağiş; Nihan Çiplakkiliç (Universitas Negeri Semarang, 2026)
This exploratory repeated-measures study examined how music tempo relates to preschool children’s visual production during open-ended painting. The study addresses a gap in multisensory art education by moving beyond passive music–color matching and examining how auditory tempo is reflected in children’s material, color, and compositional choices during artmaking. Twenty-five children aged 60–72 months from preschools in five Turkish provinces completed painting activities under fast-tempo (120–168 BPM) and slow-tempo (45–60 BPM) instrumental music conditions. Drawings were coded for color presence, color coverage, warm–cool balance, dominant color, recurring figure categories, spatial distribution, painted-area coverage, central concentration, and layering. Inter-rater reliability was assessed before consensus coding, and mixed-effects models were used to account for repeated observations within children. Tempo-related differences were most evident in color and compositional outcomes. Fast-tempo drawings showed a slightly broader color palette and greater warm-color coverage, whereas slow-tempo drawings showed greater painted-area coverage, central concentration, and layering. Figure categories, including people, rainbows, hearts, and suns, showed descriptive variation but did not remain significant after multiple-comparison correction. The findings suggest that music tempo may serve as a contextual feature of multisensory artmaking, shaping specific visual and material decisions without producing fixed symbolic or expressive styles.